Scaling Law for a Low-Pressure Gas Breakdown in a Homogeneous DC Electric Field - Lisovskiy, V.; Yakovin, S. (Journal of Experimental and Theoretical Physics Letters, 2000)
Gas breakdown in nitrogen, air, and oxygen in a dc electric field at various interelectrode distances L is studied experimentally. A scaling law for a low-pressure gas breakdown Udc=f(pL,L/R) is deduced. According to this scaling law, the breakdown voltage Udc is a function not only of the product of the gas pressure p and the gap length L, but also of the ratio of the gap length L to the chamber radius R. It is shown that, for any dimensions of the cylindrical discharge chamber (in the range of L/R under investigation), the ratio of the breakdown electric field to the gas pressure p at the minimum of the ignition curve remains constant: (Edc/p)min = const. A method for calculating the ignition curve in a cylindrical discharge chamber with arbitrary values of L and R is proposed.
Keywords: plasma physics; gas discharges